Juhuud Waliyyat al-Fushuul wa Muhaawalaatihinn Fii Raf'i Mahaarat al-Kalaam al-'Arabiyyat li al-Thaalibaat bi Ma'had Daar al-Salaam Gontor - Yoke Suryadarma; Fathiyatul Husna Riskia; Yuslina Mohamed (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2023)
When it comes to mentoring and instructing her students, the homeroom teacher has more duties and responsibilities than other teachers. The teacher's efforts are required to improve the speaking abilities of the Students. This study aims to shed light on the homeroom teacher's efforts to improve the speaking abilities of one intensive student at the Islamic Boarding School of Darussalam Gontor for Girls' first campus during the academic year 2020–2021. Interviews, observation, and written method are used in this qualitative descriptive study to gather the data. As a consequence of this study, the researcher discovered that the homeroom teacher has a significant influence in helping students in class one intensive to improve their speaking abilities. The researcher discovered additional elements that helped female students' speaking abilities, including extracurricular and classroom activities. Additionally, there are obstacles both inside and outside of the students. The pages that follow will provide a thorough explanation. This study will be helpful to the homeroom teacher at Darussalam Gontor for Girls as well as the teacher and headmaster of the school, especially in the Islamic Boarding School, as well as the following researcher.